Discriminazioni algoritmiche e tutela dei lavoratori: riflessioni a partire dall’Ordinanza del Tribunale di Bologna del 31 dicembre 2020 (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article analyses the order of the Court of Bologna of 31 December 2020 concerning the indirect collective discrimination committed by Deliveroo Italy S.r.l. against its riders through the management algorithm.
Keywords: Labour law; anti–discrimination law; algorithmic discrimination; riders; right to strike